Ni and TiO2 nanoparticles cause adhesion and cytoskeletal changes in human osteoblasts - Štefančík, Michal; Válková, Lucie; Veverková, Jana; Balvan, Jan; Vičar, Tomáš; Babula, Petr; Mašek, Josef; Kulich, Pavel; Pávková Goldbergová, Monika (Environmental science and pollution research international, 2021)
Titanium-based alloys have established a crucial role in implantology. As material deteriorates overtime, nanoparticles of TiO2 and Ni are released. This study is focused on the impact of TiO2 and Ni nanoparticles with size of 100 nm on cytoskeletal and adhesive changes in human physiological and osteoarthritic osteoblasts. The impact of nanoparticles with concentration of 1.5 ng/mL on actin and tubulin expression and gene expression of FAK and ICAM-1 was studied. The cell size and actin expression of physiological osteoblasts decreased in presence of Ni nanoparticles, while TiO2 nanoparticles caused increase in cell size and actin expression. Both cell lines expressed more FAK as a response to TiO2 nanoparticles. ICAM-1 gene was overexpressed in both cell lines as a reaction to both types of nanoparticles. The presented study shows a crucial role of Ni and TiO2 nanoparticles in human osteoblast cytoskeletal and adhesive changes, especially connected with the osteoarthritic cells. Graphical abstract.
Keywords: Adhesion; Osteoblasts; osteoblasty; buněčná adheze; Ni nanoparticles; Cell Adhesion; Humans; TiO2 nanoparticles; titan; Bone; Cytoskeleton; Nanoparticles; cytoskelet; lidé; Titanium; nanočástice